Islamic Republic of Mauritania : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Islamic Republic of Mauritania. (IMF Staff Country Reports; Country Report ;, 2007)
The staff report for the First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) for the Islamic Republic of Mauritania explains the macroeconomic outlook and fiscal policy. Despite a substantial oil revenue shortfall, the fiscal deficit target was met and significant reserves were maintained in the oil fund. The prudent monetary stance contributed to strengthening confidence in the ouguiya and reining in inflation. Mauritania needs to continue to mobilize concessional support to finance its poverty reduction strategy.